Additional record of Langea euprosopides (Coleoptera: Cicindelidae) for Peru - Bustamante-Navarrete, Abdhiel Arnaldo (2016)
A new specimen of Langea euprosopides W. Horn, 1901 is recorded from the Cusco region of Perú. The genus Langea W. Horn presently contains three species. Due to a lack of observations of members of this genus in the wild, its habits, natural history and life cycle stages are unknown. The genus is apparently endemic to Perú. Some data on the likely capture substrate and a distribution map of the species in Perú are presented.